Pengaruh Brand Image, Word Of Mouth, Dan Kualitas Produk Terhadap Loyalitas Pelanggan Pengguna Produk Skincare Npure - Larasati Arning Putri; Annisa Wahyuni Arsyad (Yayasan Pendidikan Riset dan Pengembangan Intelektual (YRPI), 2025)
This study aims to analyze the effect of brand image, word of mouth, and product quality variables on customer loyalty of NPure skincare product users, both partially and simultaneously. This study involves a population of NPure skincare users who have used Npure products for more than 3 months. The sampling technique used was purposive sampling, with a total of 100 respondents. Primary data was collected through a questionnaire survey. Data analysis was carried out using multiple linear regression techniques with the help of the SPSS for Windows application. The results showed that Brand Image, Word Of Mouth, and Product Quality have a positive and significant influence on Customer Loyalty of NPure Product Users, both partially and simultaneously.